Fatores de risco relacionados à pré-eclâmpsia - Amaral, Walter Toledo; Peraçoli, José Carlos [UNESP] (My University, 2011)
Introduction: Preeclampsia is a major cause of maternal and perinatal morbidity and mortality in Brazil and worldwide. It is a heterogeneous disorder, multifactorial, with no clear etiology and pathophysiology. The identification of risk factors for its development can assist in prevention and early diagnosis of the clinical onset of the disease Objective: To identify risk factors related to the development of preeclampsia aimed at identifying pregnant women at risk for early disease and to offer specialized treatment to them Methodology: A bibliographic survey of scientific articles indexed in the following databases: CAPES (Ovid external Link), Scientific Eletronic Library Online (SciELO), Latin American and Caribbean Health Sciences Literature (LILACS), and Medical Literature Analysis and Retrieval System Online (Medline) of the National Library of Medicine over the last tem years (2001-2011) was carried out with the addition of certain classic and priority references.

Introdução: A pré-eclâmpsia é uma das principais causas de morbimortalidade materna e perinatal no Brasil e no mundo. É uma patologia heterogênea, multifatorial, sem etiologia esclarecida e fisiopatologia complexa. A identificação de fatores de risco ao seu desenvolvimento pode auxiliar na prevenção e diagnóstico precoce do início clínico da doença. Objetivo: Identificar fatores de risco relacionados ao desenvolvimento da Pré eclâmpsia no sentido de identificar precocemente gestantes com risco para a doença e oferecer a estas, acompanhamento especializado. Metodologia: Realizou-se levantamento bibliográfico de artigos científicos indexados nas bases de dados: CAPES (Ovid external Link), Scientific Eletronic Library Online (SciELO), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), Medical Literature Analysis and Retrieval System Online (Medline) da National Library of Medicine nos últimos 10 anos (2001 a 2011), além de algumas referências clássicas e prioritárias.
Risk factors related to preeclampsia
Keywords: Pregnancy; Hypertension; Preeclampsia; Maternal Morbidity; Maternal mortality; Gravidez; Hipertensão Arterial; Pré-eclâmpsia; Morbidade Materna; Mortalidade Materna